contribution to the simulation of coupled transfers phenomenon application on the PEM Fuel cell - فرجاني عبد الفتاح, يحي عبد النور (university of Eloued جامعة الوادي, 2018)
The interest of clean environmentally friendlier and more efficient energy sources leads to the increase of interest in fuel cells, as it has no production other than water and heat. Fuel cells are electrochemical devices that are designed to directly convert, with high efficiency, the chemical energy from the reaction of the fuel (hydrogen in case of PEMFC) and an oxidant (oxygen) into electricity. In the proton exchange membrane (PEM) fuel cell study, numerical analysis of complex and coupled multi-disciplinary processes involving the subjects of fluid dynamics, heat transfer, mass transport, and electrochemistry has been attempted over the past few decades. However, the performances of the PEMFC can improve by the development of the used models and the obtained results إن الاهتمام بمصادر الطاقة النظيفة الصديقة للبيئة الأكثر كفاءة يؤدي إلى زيادة الاهتمام بخلايا الوقود ، حيث لا يوجد لديها إنتاج غير الماء والحرارة. خلايا الوقود هي أجهزة كهروكيميائية تم تصميمها للتحويل المباشر ، بكفاءة عالية ، الطاقة الكيميائية من تفاعل الوقود (الهيدروجين في حالة PEMFC) والأكسدة (الأكسجين) إلى كهرباء. في دراسة خلايا الوقود بغشاء التبادل البروتوني (PEM) ، تمت محاولة التحليل العددي للعمليات المعقدة والمتعددة الاختصاصات التي تشمل مواضيع ديناميكية السوائل ، ونقل الحرارة ، والنقل الجماعي ، والكيمياء الكهربائية على مدى العقود القليلة الماضية. ومع ذلك ، يمكن لأداء PEMFC تحسين من خلال تطوير النماذج المستخدمة والنتائج التي تم الحصول عليها.PEMFC
مذكرة ماستر في الهندسة الميكانيكة تخصص طاقوية
Keywords: CFD Fluent; Fuel cell; Modeling; Simulation; GDL.; CFD خلية وقود ; النمذجة; المحاكاة ; GDL